2005
DOI: 10.1158/0008-5472.can-04-2908
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases 9 and 10 Inhibit Protein Kinase C–Potentiated, p53-Mediated Apoptosis

Abstract: Abstractp53, a major sensor of DNA damage, is a transcription factor that, depending on its phosphorylation status, regulates the cell cycle, DNA repair, or apoptosis. The protein kinase C (PKC) family of isozymes is also implicated in cell cycle and programmed cell death (PCD) control and has recently been shown to influence p53 function. Using three human colon adenocarcinoma cell lines SW480, EB-1, and HCT116 that either lack p53 function and were engineered to express inducible wild-type p53 (wt p53), or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 52 publications
2
56
3
Order By: Relevance
“…Mitotic phases are accompanied by a highly conserved and dynamic distribution of the enzyme as from studies in neuroblastoma cells and in macrophages (Sans-Fons et al, 2010;Ganji et al, 2011). Furthermore, MMP-9 affects apoptosis by degrading apoptotic molecules, as the Kit-ligand, hence promoting cells survival (Meyer et al, 2005). In addition, MMP-9 shedding of ICAM-1 confers protection to NK and Tcell mediated cytotoxicity (Fiore et al, 2002).…”
Section: Biological Aspectsmentioning
confidence: 99%
“…Mitotic phases are accompanied by a highly conserved and dynamic distribution of the enzyme as from studies in neuroblastoma cells and in macrophages (Sans-Fons et al, 2010;Ganji et al, 2011). Furthermore, MMP-9 affects apoptosis by degrading apoptotic molecules, as the Kit-ligand, hence promoting cells survival (Meyer et al, 2005). In addition, MMP-9 shedding of ICAM-1 confers protection to NK and Tcell mediated cytotoxicity (Fiore et al, 2002).…”
Section: Biological Aspectsmentioning
confidence: 99%
“…Thus, high expression of MMP-2 and MMP-9 may be used to characterize the behaviors of colorectal carcinoma (38,39). Moreover, high colorectal MMP-9 expression has been implicated in lung metastases (40) and tumor cell resistance to proapoptotic and p53 effects, as well as poor efficacy in postoperative adjuvant chemotherapy (41). In vitro, MIF also was shown to promote cell invasiveness through macrophage secretion of MMP (42).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…Studies have demonstrated that PKC-d promotes cell death in many noncolonic cell lines, including keratinocytes (Denning et al, 1998), neutrophils (Pongracz et al, 1999), cerebral granule cells (Villalba, 1998), HL-60 and prostate cancer cells (Savickiene et al, 1999;Yin et al, 2005), but not in breast cancer cells (McCracken et al, 2003;Nabha et al, 2005). In studies in colonic cells, PKC signaling pathways are also involved in cell cycle and cell death regulation (Goldstein et al, 1995;Qiao et al, 1996;Sauma et al, 1996;Abraham et al, 1998;Perletti et al, 1998Perletti et al, , 1999Andre et al, 1999;Assert et al, 1999;Weller et al, 1999;Umar et al, 2000;Cerda et al, 2001;Lin et al, 2002;McMillan et al, 2003;Di Mari et al, 2005;Meyer et al, 2005). Several studies, including our own investigations, have demonstrated a tumor suppressor role for PKC-d in colon cancer cells, including cell cycle arrest and enhanced apoptosis (Weller et al, 1999;Cerda et al, 2001;Lin et al, 2002;McMillan et al, 2003;Perletti et al, 2004Perletti et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%